Characteristics of oral health literacy in Senegal: A cross-sectional study among women in the Department of Pikine - Serigne N. Dieng; Aïda Kanouté; Pierre Lombrail; Massamba Diouf; Sylvie Azogui-Levy (AOSIS, 2022)
Senegal having a significant prevalence of socially differentiated oral diseases, oral health literacy (OHL), an individual and social resource, should be considered alongside a remedial response. This work aimed to analyze women's OHL characteristics. A cross-sectional study on 315 women in Pikine County was carried out, using the Oral Health Literacy-Adult Questionnaire (OHL-AQ) for the OHL data collection and a questionnaire for the women's socioeconomic characteristics data. These women had an OHL average score of 6.5±3.1 and a median of 6. Among them, 56.5% had a seemingly low OHL level, a little over 68.9% had a score above the median as regards the "listening, communication and understanding" aspect, 58.4% to "decision making", 55.2% to "understanding numbers" and 33% to "reading and understanding". According to a multivariate analysis, secondary and higher educated women (p0.001) with an active social network (p0.023), in a wealthy household (p0.0001) and of nuclear household type (p0.036) had a higher OHL level. Women in Pikine have low OHL and are from working-class households. Therefore, oral health policies must take into account the women's social network contribution to the OHL improvement.